Intact sensorimotor rhythm abilities but altered audiovisual integration in cochlear implant users - Olivier Valentin; Nicholas Elgin Vernam Foster; Bastien Intartaglia; Marie-Anne Prud’homme; Marc Schönwiesner; Sylvie Nozaradan; Alexandre Lehmann (PLoS ONE, 2025)
Perception of rhythm significantly impacts various aspects of daily life, including engaging with music, discerning speech prosody nuances, and coordinating physical activities like walking and sports. Numerous studies in cognitive sciences have highlighted that human rhythmic synchronization is more precise when responding to auditory rhythmic stimuli than to visual ones when the timing cues are identical. However, deaf individuals were shown to display a heightened proficiency in synchronizing their movements with visual timing cues, outperforming hearing controls (HC). Furthermore, it was demonstrated that cochlear implant (CI) users can synchronize their movements with the rhythm of unpitched drum tones. These findings raise an important question: do CI users possess a visual synchronization advantage from their pre-implant deafness, while maintaining auditory synchronization skills comparable to those of HC? Alternatively, does the neural reorganization post-implantation negate the visual synchronization advantage acquired before the implant? This study aims to answer these questions by using a sensorimotor synchronization task to probe multisensory processing abilities in CI users. Specifically, we assessed unimodal and multimodal auditory and visual abilities in CI users compared to HC using a finger tapping synchrony task with four isochronous stimulus conditions: an auditory metronome, a visual metronome, a synchronous presentation of both the auditory and visual metronomes at the same tempo, and an asynchronous presentation of the auditory and visual stimuli at differing tempos. Synchronization to auditory stimuli surpassed synchronization to visual stimuli in both groups. CI users and HC demonstrated similar unisensory synchronization consistency within the visual and auditory conditions. While HC enhanced their consistency in the audio-visual synchronous condition compared to the unisensory visual condition, CI users did not display the same improvement. Furthermore, the interference from incongruent auditory information in the asynchronous condition was comparable in HC and CI users. This study highlights that, although pitch processing is known to be impaired in CI users, our findings suggest that rhythm processing remains relatively spared. As anticipated, CI users demonstrate similar auditory rhythmic synchronization skills to those of HC, in line with existing research. Moreover, we find that, unlike deaf individuals, CI users do not exhibit an advantage in visual rhythmic synchronization, which may be due to the relatively few CI users in the study who had early prolonged pre-implantation deafness. The observed shift in audio-visual integration among CI users suggests that post-deafness or post-implantation reorganization of their auditory cortex may impede the effective integration of temporal auditory stimulation from the implant and visual information.